Atorvastatin Improves Inflammatory Response in Atherosclerosis by Upregulating the Expression of GARP - Xiaoqi Zhao; Yuzhou Liu; Yucheng Zhong; Bo Liu; Kunwu Yu; Huairui Shi; Ruirui Zhu; Kai Meng; Wei Zhang; Bangwei Wu; Qiutang Zeng (Mediators of Inflammation)
Regulatory T cells play an important role in the progression of atherosclerosis. GARP is a newly biological membrane molecule existed on activated Tregs, which is related to the release of TGF-β. The antiatherosclerosis effects of statins partly depend on their multiple immune modulatory potencies. In this paper, we present that atorvastatin could upregulate the expression of GARP and TGF-β in CD4+ T cells and increase the numbers of CD4+LAP+ and CD4+Foxp3+ regulatory T cells in ApoE−/− mice. Also, we indicate that atorvastatin promotes the aggregation of GARP+ and Foxp3+ cells and secretory of the TGF-β1 in atherosclerotic plaques. Furthermore, we prove that atorvastatin could delay the procession of atherosclerosis and improve the stability of atherosclerotic plaques. Interestingly, we report that inhibition of GARP distinctly inhibits the anti-inflammatory effects of atorvastatin. We conclude that atorvastatin improves the inflammatory response in atherosclerosis partly by upregulating the expression of GARP on regulatory T cells.